2017
DOI: 10.5114/aoms.2016.58636
|View full text |Cite
|
Sign up to set email alerts
|

The rs2228145 polymorphism in the interleukin-6 receptor and its association with long-term prognosis after myocardial infarction in a pilot study

Abstract: IntroductionInterleukin-6 (IL-6) is a cytokine with a complex function that is described as both pro- and anti-inflammatory. One factor that influences its function is the rs2228145 A/C single nucleotide polymorphism (SNP) of the IL-6 receptor (IL6R) gene. C allele carriers have a decreased inflammatory response and decreased prevalence of ischemic heart disease. The aim of the study was to investigate the association of the rs2228145 SNP of the IL6R gene with long-term total mortality in patients with ST-elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Of note, it has been demonstrated that SNPs in the IL6R gene (e.g., Asp358Ala [rs2228145]; ref. 33) can influence inflammation in the context of various inflammatory (34)(35)(36) and cardiac disorders (37)(38)(39). In summary, these findings offer insights into the role of the ectopic membrane-bound IL6R upregulation in PA-SMCs in PAH.…”
Section: Discussionmentioning
confidence: 80%
“…Of note, it has been demonstrated that SNPs in the IL6R gene (e.g., Asp358Ala [rs2228145]; ref. 33) can influence inflammation in the context of various inflammatory (34)(35)(36) and cardiac disorders (37)(38)(39). In summary, these findings offer insights into the role of the ectopic membrane-bound IL6R upregulation in PA-SMCs in PAH.…”
Section: Discussionmentioning
confidence: 80%
“…Several studies have reported an association between the IL-6 gene (-174G>C) polymorphism and CAD, HF [13,14]. However, other studies have reported no such relation [15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of this allele in Poles is very close to the average (36.0%) of five European-derived populations from the 1000 Genomes project, ranging from 33.2% to 40.1%. This highlights the genetic variability across populations and the need for a nuanced understanding of genetic factors in disease predisposition [51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%